2007
DOI: 10.1007/s11606-007-0135-2
|View full text |Cite
|
Sign up to set email alerts
|

Screening Patients with a Family History of Colorectal Cancer

Abstract: OBJECTIVES:To compare screening practices and beliefs in patients with and without a clinically important family history. DESIGN:We mailed a brief questionnaire asking about family history and a second, longer survey asking about knowledge of and beliefs about colorectal cancer to all respondents with a family history and a random sample of respondents without a family history of colorectal cancer. We reviewed electronic medical records for screening examinations and recording of family history. PARTICIPANTS:O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 29 publications
1
37
0
Order By: Relevance
“…We found that nearly three-fourth of individuals with an established elevated risk for CRC were not aware of their CRC risk and the significance of undergoing screening tests, comparable with those outlined in American, Canadian and also Asian studies 79 11…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…We found that nearly three-fourth of individuals with an established elevated risk for CRC were not aware of their CRC risk and the significance of undergoing screening tests, comparable with those outlined in American, Canadian and also Asian studies 79 11…”
Section: Discussionsupporting
confidence: 68%
“…11 Although people with an elevated risk of CRC were found to be more compliant to screening guidelines compared with average-risk individuals,12 they are also underusing CRC screening 9. Data of more than 6800 participants in the USA showed that only 45% of individuals with a strong family history of CRC had undergone CRC screening and over 50% were not aware that they should be screened at an early age compared with the moderate-risk people 11…”
Section: Introductionmentioning
confidence: 99%
“…In any case, family history of colorectal cancer is often not recorded in the medical record nor used in screening decisions. 19 The risk of developing colorectal cancer is also related to behavioral risk factors-consumption of processed or red meat and fruits and vegetables, as well as smoking, alcohol use, obesity, exercise, and the use of aspirin-like drugs, folic acid, postmenopausal estrogens, calcium, and vitamin D. 20 Although each of these factors seems to be associated with a small relative risk, when taken together they may define subgroups of patients at substantially different risk, every bit as different as for family history alone. 21 Multivariable risk scores have received little attention from investigators so far and have not been incorporated into clinical practice guidelines.…”
Section: Risk Stratificationmentioning
confidence: 99%
“…Mack et al . (2009) reported a certain degree of uncertainty by people regarding their personal risk level in relation to their family history, although in most similar studies people were aware of their increased risk relative to the general population (Fletcher et al . 2007; Harris & Byles 1997; Harris et al .…”
Section: Introductionmentioning
confidence: 99%